ANMCO POSITION PAPER: The cardiological clinical activities in the transition phase of the COVID-19 pandemic. (27th August 2020) - Valente, Serafina; Colivicchi, Furio; Francese, Maura Giuseppina; Di Lenarda, Andrea; Roncon, Loris; Murrone, Adriano; Caldarola, Pasquale; Bilato, Claudio; Amodeo, Enzo; Aspromonte, Nadia; Cipriani, Manlio; Domenicucci, Stefano; et al.
Abstract: Infections by SARS CoV2 - COVID-19 became in a short time a worldwide health emergency. The present SARS-CoV-2 pandemic induced in a short time, an unprecedented impact on public health and on the pre-existing care pathways. In order to appropriately address this epidemiological emergency, urgent solutions were needed, such as remodelling or stopping hospitalization and deferrable clinical activities to avoid spreading the SARS-CoV-2 infection. After the first emergency lockdown phase, care pathways must guarantee healthcare to patients and preserve the safety of the healthcare personnel and of all the other subjects that refer to the cardiological surgeries. Rigorous prescriptive appropriateness of the requested exams with consequent reduction of unnecessary examinations is an essential requirement to preserve prioritized diagnostic and care pathways to patients in need, minimizing the risks connected to the SARS-CoV-2 contagion in hospitals. Telemedicine services represent a valid answer to cardiovascular disease patients' need for care and assistance, including those in quarantine and voluntary isolation. These services successfully contribute to fight the spread of the virus guaranteeing at the same time therapy and support through remote services that must therefore be considered a resource to be implemented and enhanced. This document has to be used by the healthcare personnel working in hospitals and in district offices, if applicable, and aims at managing patients, in complete safety and considered not suspect/not probable ('not at risk') of SARS-CoV-2 infection, eligible for diagnostic activity and subsequent therapy in outpatient surgeries. In particular, this document provides indications for patient evaluation to prevent COVID-19 exposure, gives general indications on managing appointments and waiting rooms, on how to strictly adhere to environmental safety measures, on the proper use of Individual Protective Equipment (IPE). It also provides specific indications for outpatient service procedures, like electrocardiogram, cardiologic examination, cardiologic checkup, Dynamic Holter Electrocardiogram, Transthoracic Echocardiography, Echo Stress, Transoesophageal Echocardiography, Bike Ergometer stress test, Ergospirometry, Outpatient Checkup of implantable electronic cardiac devices.